(untitled) (BIRDEM Medical Journal, 2020)
In south-east Asia, there has been a common belief, mainly in rural areas, that ingesting raw fish gall bladder can help cure certain health problems. Unfortunately, raw fish bile has both nephrotoxic and hepatotoxic effects. In this report, we present a case of 42-year-old man, who presented with acute kidney injury and jaundice. Meticulous history revealed that his ailment resulted from raw Rohu fish gallbladder ingestion. Birdem Med J 2021; 11(1): 70-71